2018
DOI: 10.1002/2017gl076554
|View full text |Cite
|
Sign up to set email alerts
|

A “Geodetic Gap” in the Calabrian Arc: Evidence for a Locked Subduction Megathrust?

Abstract: Subduction of old Ionian seafloor beneath the Calabrian Arc (southern Italy) is the geological process with the greatest mass flux in the central Mediterranean, yet its seismogenic behavior is largely obscured. No unambiguous evidence of subduction‐related earthquakes exists in historical times, and local GPS velocities indicate very low strain rates. Nevertheless, the region hosted some of the deadliest normal‐faulting earthquakes of the entire Mediterranean basin. We show that the low strain rates recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The migration of the Calabrian Arc subduction system have significantly slowed down over time (Wortel and Spakman, 2000;Goes et al, 2004;Rosenbaum and Lister, 2004;Faccenna, 2005;Mattei et al, 2007) and it is still weakly active (Palano et al, 2017). This characteristic of the subduction process provides a critical constraint for modeling the present day activity and potential earthquake production of the slab interface (Carafa et al, 2018;Nijholt et al, 2018). Both the propagation and displacement rates of the AFS also significantly slowed down over time, implying that the subduction process and AFS development are interdependent.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The migration of the Calabrian Arc subduction system have significantly slowed down over time (Wortel and Spakman, 2000;Goes et al, 2004;Rosenbaum and Lister, 2004;Faccenna, 2005;Mattei et al, 2007) and it is still weakly active (Palano et al, 2017). This characteristic of the subduction process provides a critical constraint for modeling the present day activity and potential earthquake production of the slab interface (Carafa et al, 2018;Nijholt et al, 2018). Both the propagation and displacement rates of the AFS also significantly slowed down over time, implying that the subduction process and AFS development are interdependent.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…The identification and characterization of lateral terminations of the slab was mainly based on tomography data and on the geologic and geodetic evidence of active tectonics, along with a rather abrupt lateral termination of intraslab seismicity (Guarnieri, 2006;Del Ben et al, 2008;Orecchio et al, 2014Orecchio et al, , 2015Barreca et al, 2016;Chiarabba and Palano, 2017;Cultrera et al, 2017;Milia et al, 2017;Palano et al, 2017;Carafa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In more active areas, like subduction zones, a more complex interplay between seismicity and strain is possible. Carafa et al (2018) investigating the Calabrian Arc proposed that the low strain rates observed by GPS together with large seismic moment release may be explained by a model with high interseismic coupling and low seismic coupling of the subduction interface.…”
Section: Introductionmentioning
confidence: 99%
“…Available estimates of the convergence rates in these subduction zones are very variable, and we recall just some of them here. The Calabrian Arc convergence rate is estimated at 5 mm/year by Devoti et al (2008) and recently at 1.5-1.6 mm/year if creeping, or 2:7 À 3:0 if temporarily locked by Carafa et al (2018). The Hellenic Arc convergence rate is estimated at 23 mm/year in the Ionian Islands (Hollenstein et al 2008), 35 mm/year in the western Figure 1 a Rigidity profiles as a function of the depth computed from the end-member case of Bilek and Lay (1999) (blue curve) and interpolating the PREM (Dziewonski and Anderson 1981) values (green line).…”
Section: Subduction In the Mediterraneanmentioning
confidence: 99%
“…The values of the coupling coefficients in these three subduction zones are also highly debated. In the Calabrian Arc two competing interpretations-ranging from partially-locked to unlocked or inactive-were recently proposed (Carafa et al 2018;Nijholt et al 2018). In the Hellenic Arc interpretations range from full locking (Ganas and Parsons 2009) to low coupling (Shaw and Jackson 2010;Vernant et al 2014), but also the presence of important along-strike coupling variations was proposed (Laigle et al 2004).…”
Section: Subduction In the Mediterraneanmentioning
confidence: 99%